Pengaruh Permainan Round of Dragon Snake Rainbow terhadap Peningkatan Kemampuan Berpikir Kritis pada Peserta Didik : The Effect of the Round of Dragon Snake Rainbow Game on Improving Critical Thinking Skills in Students - Siti Hafizah; Ali Rachman; Nina Permata Sari (ITScience (Information Technology and Science), 2025)
Critical thinking is one of the most important 21st-century skills students need to develop to analyse, evaluate, and make rational decisions. However, in practice, students' critical thinking skills remain low because learning tends to be one-way and lacks exploratory activities. The gap between the demands for developing critical thinking skills and the implementation of learning in schools is the basis for this research. This study aims to determine the effect of the Round of Dragon Snake Rainbow game on the critical thinking skills of eighth-grade students at SMP Negeri 17 Banjarmasin. The study used a quantitative approach within the influence research type. The research subjects were 29 students selected through purposive sampling. The research instrument was a Likert scale questionnaire that had been tested for validity and reliability. Data were analysed using prerequisite tests (normality, homogeneity, and linearity) and hypothesis testing with simple linear regression and a t-test in SPSS. The study results indicate that the Round of Dragon Snake Rainbow game has a positive and significant effect on students' critical thinking skills, with a significance level < 0.05 (p = 0.001) and a t-value (3.707) greater than the t-table (2.052). These findings indicate that educational games can create active, interactive, and enjoyable learning experiences, thereby fostering greater critical thinking among students. These findings indicate that educational games can create active, interactive, and enjoyable learning experiences, thereby fostering greater critical thinking among students. Thus, the Round of Dragon Snake Rainbow game can serve as an alternative medium for guidance and counselling to develop critical thinking skills in schools.